PENGARUH PROMOSI JABATAN DAN MOTIVASI KERJA KARYAWAN TERHADAP PRESTASI KARYAWAN STUDI KASUS PADA PERUM PERCETAKAN NEGARA REPUBLIK INDONESIA (PNRI) - Syilvia, Dini (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2021)
This research aim to know the influence of promotion of job & motivation of employees on the performance of Perum Percetakan Negara Republik Indonesia (PNRI). The population of this study using sampling method with Slovin formula and its spreading using questionnaire data questionnaire (questionnaire) as much as 77 employees. Data obtained from distributing questionnaires to 77 respondents. To answer the formulation of problem, purpose, and hypothesis of research, hence the analysis used is using multiple linear regression method based on SPSS. Based on the results of SPSS can be concluded that promotion of employment and motivation of employees have a significant effect partially or simultaneously on employee performance.